Analisis Budaya Kerja dan Kepuasan Karyawan dalam Mendukung Kualitas Layanan: Studi Kasus Budaya Kerja di Restoran X - Revitha Regina Rejadi; Brillyan Lorinanto; Agoes Tinus Lis Indrianto (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to understand the dynamics of work culture and employee satisfaction in shaping service quality at Restaurant X. The background of this research is based on the increasing competition within the restaurant industry, which demands innovation, service consistency, and effective human resource management, making organizational work culture and employee satisfaction important internal factors. This study employs a qualitative approach using a case study method to obtain an in-depth understanding within the operational context of the organization. Data were collected through semi-structured interviews with management and employees, as well as non-participatory observations of service activities. Data analysis was conducted thematically using an interactive model. The findings indicate that the internalization of customer-oriented work culture values, employee satisfaction through a supportive work environment, and the integration of both factors mutually reinforce one another in promoting responsive, consistent, and empathetic service practices. This study illustrates that the relationship between work culture and employee satisfaction plays a strategic role in supporting responsive and customer-oriented service practices.